Beyond text learning through arts-based research - Adams, Jeff; Owens, Allan (Intellect Books, 2021)
This original new book represents a variety of art forms across different professional contexts. Its focus is on the ways that educational practitioners and leaders from a range of cultures, disciplines, professions and organizations practice arts-based research, and it explores how these can enable innovative means of learning and enhance professional and organizational development. This vibrant project allowed for long term systematic conversations between a large and unusually diverse group of twenty-nine people from eight organisations in six countries. It was unusually diverse in many senses: for some the word ‘data'meant little, for others it was central to their daily work; for some artistic practice was core, while for others the arts were a means to an end; while some were social entrepreneurs running their own companies others were researching in universities and a number were doing both; some were working within the STEM disciplines of business, management, engineering, science, technology, sustainability and the built environment, others were in the social sciences of social and health care, education and youth work while others were engaged in rapid or long term social and cultural action as a means of resisting state violence and military occupation; some worked in one of the safest countries on the planet, others in one of the most tear-gassed refugee camps in the world. Within these professional groups there were also ranges of experience, for example senior researchers, early career researchers, PhD students, seasoned professional artists and newcomers to arts forms. Whilst the main communication of this group was English, six other major languages were spoken, Estonian, Finish, Catalan, Spanish, Arabic and key stakeholders bought Swedish and Japanese into the space. This meant that while the conversations in and about arts-based practice were transnational, interdisciplinary and systematic, they had all the messy, troubled-ness that the intercultural on all of the above levels brings with it. This unique and exciting collection discusses how creative arts practices can have a significant impact on research across a range of international contexts, drawing on their own field of research and educational experience. For instance, drama, music, dance and visual arts can be used to understand how learners internalise concepts, reflect on how decisions are made in the midst of action in leadership education, or investigate the use of the intuitive alongside the rational and analytical in their educational experience. Non-textual arts-based forms of research can also provide modes of investigation into pedagogical and professional practices when applied to fields that normally lie outside of the arts. Its greatest strengths are its focus on arts-based research as a way of learning in a variety of contexts, and often in collaboration. Its consistent theoretical, artistic and professional engagements make it a very readable and engaging read. The representation of a variety of art forms across different professional contexts means that this book will have appeal to several readerships in higher education, including the following groups. Academics and practitioners using arts-based methods in organisation and business settings. Researchers in the arts and researchers generically in the social sciences, humanities and arts. University students of the arts, education and professional studies, especially those interested in the wider international and intercultural diversity of research methodologies. Those working in international research teams using any form of qualitative research will also find this collection very interesting. It also has potential interest for groups outside higher education with an interest in arts-based research – for example community groups looking to explore collaborative projects.